THE INFLUENCE OF PROFITABILITY AND LEVERAGE TOWARDS TAX AGGRESSIVENESS - Purnamasari, Dyah (International Journal of Psychosocial Rehabilitation, 2020)
This research points to dictate the effect of profitability and leverage on tax aggressiveness in the consumer goods manufacturing corporations listed on the IDX in the 2016-2018 period. The research method used in this study is the experimental method. The population in this study consisted of 56 manufacturing corporations in the consumer goods sector, and the corporations that were sampled in this study were 16 corporations. The results showed that profitability and leverage had a partial and simultaneous effect on tax aggressiveness in the consumer goods manufacturing corporations listed on the IDX for the period of 2016-2018. The magnitude of the effect of simultaneous profitability and leverage on tax aggressiveness is 80.5678%.